Données préliminaires concernant l'élevage dirige des poissons marins au littoral roumain de la Mer Noire - Udrea, Valerian (Cercetări Marine - Recherches Marines, 2026)
The attempts of the Mugil cephalus. M. auratus and M. sailens conducted growth, together with Platichtys flesus luscus and Acipenseridae have demonstrated that these species are adapting to freshwater ponds growing conditions. In this paper are presented the main biotechnical parameters resulted from experiences such as the population density on hectare, the yearly rhythm of growth, the artificial food consumption per one kilo fish meat and the hectare productivity.